The European Natural Gas Market: Imports to Rise Considerably - Hella Engerer; Manfred Horn (Weekly Report, 2009)
Since the late 1990s, natural gas has been the second most important source of energy in the European Union after oil. Current forecasts predict that the demand for natural gas will continue to rise over the long term. As the production of natural gas in the EU has already passed its peak and will drop in coming years, natural gas imports will have to rise considerably. To ensure according supplies is possible in the long run, as approximately 80% of the world's natural gas reserves are located within the economic reach of the EU-primarily in the former Soviet Union and Middle East. A supply of imported natural gas adequate to cover declines in EU production is contractually guaranteed through 2020. Additional projects will permit an increase in natural gas consumption in the EU of 20 to 30%. By 2020, 80% of the EU's supply will come from imports. Russia will remain by far the largest supplier, followed by Norway and Algeria. Security concerns are raised by the importation of natural gas from a small handful of suppliers. While the regional diversification of imports is only possible to a limited extent, the construction of a pipeline to connect Europe with natural gas rich nations on the Caspian Sea and in the Middle East would be a step in the right direction. The expansion of capacities for production, transport and storage of liquified natural gas (LNG) could also help to augment diversification.
Keywords: Q41; L12; L13; 330; Natural gas; LNG; Import dependence; Reserves; Pipelines